A Rat Model of Neurocysticercosis-Induced Hydrocephalus: Chronic Progressive Hydrocephalus with Mild Clinical Impairment - Hamamoto Filho, Pedro Tadao [UNESP]; Fogaroli, Marcelo Ortolani [UNESP]; Oliveira, Marcelo Augusto Chiantelli [UNESP]; Oliveira, Cristiano Claudino [UNESP]; Batah, Sabrina Setembre; Fabro, Alexandre Todorovic; Vulcano, Luiz Carlos [UNESP]; Bazan, Rodrigo [UNESP]; Zanini, Marco Antônio [UNESP] (Elsevier, 2019)
Background: Hydrocephalus is the most common complication of extraparenchymal neurocysticercosis, combining obstructive and inflammatory mechanisms that impair cerebrospinal fluid circulation. Methods: We studied the long-term progression of neurocysticercosis-induced hydrocephalus in a rat model. We generated an experimental rat model of neurocysticercosis-induced hydrocephalus by cisternal inoculation of cysts or antigens of Taenia crassiceps and compared it with the classic model of kaolin-induced hydrocephalus. We used 52 animals divided into 4 groups: 1) control, 2) neurocysticercosis-induced hydrocephalus by cysts or 3) by antigens, and 4) kaolin-induced hydrocephalus. We studied behavioral, radiologic, and morphologic alterations at 1 and 6 months after inoculation by open field test, magnetic resonance imaging, and immunohistochemical localization of aquaporin-4 (AQP-4). Results: Behavioral changes were observed later in neurocysticercosis-induced than in kaolin-induced hydrocephalic rats (P = 0.023). The ventricular volume of hydrocephalus induced by experimental neurocysticercosis progressively evolved, with the magnetic resonance imaging changes being similar to those observed in humans. Periventricular inflammatory and astrocytic reactions were also observed. AQP-4 expression was higher in the sixth than in the first month after inoculation (P = 0.016) and also occurred in animals that received antigen inoculation but did not develop hydrocephalus, suggesting that AQP-4 may constitute an alternative route of cerebrospinal fluid absorption under inflammatory conditions. Conclusions: Our neurocysticercosis-induced hydrocephalus model allows for the long-term maintenance of hydrocephalic animals, involving mild clinical performance impairments, including body weight and behavioral changes.
Keywords: Hydrocephalus; Kaolin; Neurocysticercosis; Taenia crassiceps; Ventricular dilatation